Author Correction: Analysis of mutations in pncA reveals non-overlapping patterns among various lineages of Mycobacterium tuberculosis - Ramani Baddam (Nature Portfolio, 2018)
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has not been fixed in the paper.